Estudos de sistemas multicomponentes de Efavirenz - Luz, Marcelo Augusto Moraes da (2022)
The solubility and dissolution of drugs that are poorly soluble in water are influencedbytheir particle size, crystalline structure and physical form, which adversely affect formulation processes in terms of bioavailability and efficacy. Among all the possiblemodifications, multicomponent crystals, such as cocrystals and eutectic compositions, have been successfully used to improve drug solubility. In this context, this study aimedto prepare and characterize efavirenz multicomponent systems (EFV). EFVis anantiretroviral drug from the class of non-nucleoside reserve transcriptase enzymeinhibitors, of low solubility, used in the treatment of infection caused by HIV. Sevenpossible coformers were evaluated in these multicomponent assays: Saccharin (SAC), L-valine (VAL), Caffeine (CAF), Cysteine (CIST), Tryptophan (TRIP), Theobromine(TEO), and 3-Aminobenzoic acid (3AB). The results indicate four possible newmulticomponent systems, where the EFV/VAL-CO and EFV/3AB-COsystems standout, with possible cocrystal formation and EFV-CAF and EFV SAC, with formationof a eutectic system in which these systems may show improvements in solubility, dissolution rate, bioavailability and physical stability, in addition to improving other essential drug properties, such as fluidity, chemical stability, compressibilityandhygroscopicity. The samples were characterized by Fourier transforminfraredspectroscopy (FTIR), differential scanning calorimetry (DSC) and X-ray diffraction(PXRP).